Strengthening Adolescent Health Literacy through an Integrated Educational Approach Based on Video and Booklet Media in Vocational High Schools - Pradana, Anastasia Intan (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: This study aimed to examine the effectiveness of an integrated educational approach using video and booklet media in strengthening adolescent reproductive health literacy in a vocational high school. Methodology: A quasi-experimental pretest–posttest control group design was employed involving 28 Grade X students, equally divided into experimental (video-based education) and control (booklet-based education) groups. Health literacy was measured using a validated and reliable 28-item questionnaire (Cronbach’s Alpha = 0.851). Data were analyzed using paired t-tests and independent t-tests with a significance level of p < 0.05. Main Findings: Both interventions significantly improved health literacy scores. The experimental group showed a mean increase of 7.86 points (16.21 ± 2.45 to 24.07 ± 1.98; p < 0.001), while the control group improved by 4.21 points (15.93 ± 2.37 to 20.14 ± 2.11; p < 0.001). The difference in mean improvement between groups was statistically significant (p < 0.001), indicating greater effectiveness of video-based education. Novelty/Originality of this study: This study advances prior research by framing reproductive health education within a health literacy strengthening paradigm and by comparatively evaluating integrated audiovisual and printed media approaches in a vocational high school context, which remains underexplored in adolescent health promotion research.